The impact of the molecular weight of dextran on formation of whey protein isolate (WPI)–dextran conjugates in fibers produced by needleless electrospinning after annealing. Issue 4 (15th March 2018) - Turan, Deniz; Gibis, Monika; Gunes, Gurbuz; Baier, Stefan K.; Weiss, Jochen
Abstract : The conjugation reaction of electrospun fibers of a mixture of whey protein isolate (WPI) and dextran using different molecular weights (40, 70, and 100 kDa) and mixing ratios was studied. Abstract : The conjugation reaction of electrospun fibers of a mixture of whey protein isolate (WPI) and dextran using different molecular weights (40, 70, and 100 kDa) and mixing ratios was studied. This study includes the electrospinnability of a mixture of WPI and dextran, and the conjugation reaction between them via the initial stage of the Maillard reaction. The WPI–dextran fibers were characterized using optical and transmission electron microscopy. The covalent attachment of dextran to WPI was confirmed using sodium-dodecyl-sulfate-polyacrylamide gel-electrophoresis with protein and glycoprotein staining. Both 70 and 100 kDa of dextran and WPI at mixing ratios of 2 : 1 and 3 : 1 in phosphate buffer (30 mM, pH 6.5) were electrospun using needleless electrospinning. The solution concentration of the mixture was 50 wt% (33.3/37.5 wt% for dextran/16.5/12.5 wt% for WPI). The optimal conjugation conditions chosen from the experiments were a mixture of dextran (70 kDa)–WPI at 3 : 1 (75% relative humidity, 60 °C, 48 h).